The Effectiveness of The Role Playing Technique to Train The Student's Speaking Ability of Grade IX of SMP Plus Al-Ishlah - Wahyuni Abtiyasari; Khoirul Wafa; Moh. Zainuddin; Wahyuni Abtiyasari; Khoirul Wafa; Moh. Zainuddin (INTENS (International Journal of English Education and Linguistics), 2025)
The researcher intended to use the Role-play approach due to the low English speaking ability of class IX students at SMP Plus Al-Ishlah. The purpose of this study is to collect empirical data on the usefulness of the role-playing approach in training their speaking abilities. This research used a quantitative method and was conducted in two different class groups, namely the experimental and control classes with a quasi-experimental design. The researcher conducted the study during four meetings the first for the pre-test, the second and third for the treatment using Role Play technique, and the fourth for the post-test. The theory from Role Play according to (Shabani, 2010) is Zone of Proximal Development (ZPD) is a concept from the work refers to the range of tasks that a learner can perform with the help of a more knowledgeable individual. The t-test results show a T count value of (6.48) with a T table of (2.021) with a df of 45 students and a significance level of 0.05 or 90%. It indicates Ha is approved because "role playing has a significant effect on the speaking ability of experimental class students”. Furthermore, the additional data result from the observational data is the experimental class that was taught through role play performed a little better than the control class that was taught without role play. And then from interviews obtained data shows positive responses from several students who were interviewed regarding the role play technique. So, the role play approach has significant effects in training students' speaking abilities.